Disruption of water and electrolyte metabolism in patients with ureteral stones after contact lithotripsy - V. N. Pavlov; A. M. Pushkarev; A. V. Alekseyev; I. G. Rakipov; D. R. Musin; A. A. Izmailov (Бюллетень сибирской медицины, 2012)
Urolithiasis is one of the most common urologic diseases, and 50% of patients with urolithiasis have ureteral stones. As with ureterolitiaze and in contact lithotripsy has been established development of glomerular and tubular dysfunction, which causes up to 9% of complications. Investigation of the parameters water-electrolyte metabolism carried out 52 patients with urolithiasis before and after contact ureterolitotripsi. Once installed KLT increase in glomerular filtration rate by 61% of the daily creatinine excretion — a 43% urea — 21%, sodium — 28%, chlorides — 55%, the concentration of ACTH — 53% of cortisol — 11%. In the urine increases the concentration of indicators of the glomerular and tubular dysfunction mikroalbumina 3 times, β2-microglobulin was 4,5 times, Ngala was 58%. The identified changes areapparently caused by intrarenal mechanisms only, because the major hormonal systems that regulate water and electrolyte metabolism, did not significantly change the parameters of its operation.